A Theory of Aesthetic Justice - Peipert, John Devin (2007)
Theories of distributive justice give us the appropriate determination of who ought to have what, where ?who? are the members of society and ?what? are social goods and burdens. Traditionally, social goods have taken the form of rights and privileges, as well as more tangible economic goods. However, it is not clear that these are the only kinds of social goods relevant to justice. There is a substantial body of literature showing that environmental benefits and burdens can and should be thought of as social goods. In this paper, I will argue that we ought to make a comparable extension for aesthetic benefits and burdens. Specifically, I will show that aesthetic goods are objects of significant public interest, and therefore must be subject to our principles of justice. I begin by explaining and evaluating a theory of aesthetic justice offered by Monroe Beardsley. I will expand this theory by showing its broad applicability to myriad examples, especially to aesthetic objects in nature. Then I will show that this theory is compatible with two leading conceptions of justice: John Rawls?s liberal conception and Michael Walzer?s communitarian conception. In doing so, I will show that the theory of aesthetic justice must be taken seriously by those who have these philosophical commitments